Using innovative narrative therapies with children who witness intimate partner violence - Prahbhjot Malhi; Bhavneet Bharti (Wolters Kluwer Medknow Publications, 2022)
Background: Intimate partner violence (IPV) is a form of abuse in which one partner causes physical, psychological, or sexual harm to the other, in the relationship. Exposure of children to this kind of domestic abuse is quite common in India, though not openly discussed. The management of children who present with functional somatic symptoms (suspected to be psychogenic in nature) is extremely challenging, especially since the history of IPV is not easily forthcoming. This case series highlights the evocative power of trauma-creative narrative interventions, such as poetry writing and story-telling, that help children express their fears and distress in a safe environment. This in conjunction with other modalities of management helps in their healing. Clinical Description: We present three children presenting with various functional somatic symptoms belonging to dysfunctional families. Comprehensive in-depth interviews, psychological assessment, and kinetic family drawings helped us assess each case, elicit the history of IPV, and understand the nature of the individualized fears and distress being experienced. Management and Outcome: The primary interventions used were creative narrative interventions such as asking the children to draw, write poems, and/or tell stories about their family and the situations they were experiencing. This helped them express their feelings of helplessness and latent anger arising from witnessing these violent events. Facing their fears in a safe environment resulted in successful resolution of somatic symptoms of all the three over time. This healing was reflected in the change in expressions via the art, poems, and written/oral narrations. Other strategies like provision of psychoeducation, highlighting the connection between symptoms and the underlying trauma, referral for marital counselling, and improving social support were also used. Conclusions: Pediatricians should have a high index of suspicion of the possibility of psychosomatic conditions when their patients display inexplicable manifestations that do not fit into any recognizable clinical phenotype, either by description or after investigation. These children and adolescents should be referred for a psychological evaluation and further eclectic management. The use of creative narrative therapies in conjunction with other modalities can lead to successful resolution of functional somatic symptoms.